2024
DOI: 10.1111/1750-3841.16948
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers based on zein and red onion bulb extract (Allium cepa, L.): Volatile compounds, hydrophilicity, and antioxidant activity

Elder Pacheco da Cruz,
Juliani Buchveitz Pires,
Estefani Tavares Jansen
et al.

Abstract: Onion is rich in bioactive and volatile compounds with antioxidant activity. However, the pungent odor of volatile compounds (VOCs) released restricts its use. The encapsulation of red onion extract by electrospinning is an alternative to mask this odor and protect its bioactive compounds. The main objective of this study was to encapsulate red onion bulb extract (ROE) in different concentrations into zein nanofibers by electrospinning and evaluate their thermal, antioxidant, and hydrophilicity properties. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The zein nanofibers from a single-fluid electrospinning often have a flat morphology (Cruz et al, 2024;Juri c et al, 2023). Yang et al reported a modified coaxial electrospinning process, in which only unspinnable acetic acid was used as sheath fluid (Yang et al, 2013).…”
Section: Electrospun Nanofibrous Shapes For Drug Releasementioning
confidence: 99%
“…The zein nanofibers from a single-fluid electrospinning often have a flat morphology (Cruz et al, 2024;Juri c et al, 2023). Yang et al reported a modified coaxial electrospinning process, in which only unspinnable acetic acid was used as sheath fluid (Yang et al, 2013).…”
Section: Electrospun Nanofibrous Shapes For Drug Releasementioning
confidence: 99%